Non-invasive assessment of cardiac percutaneous occluders healing process using computed tomography imaging: a proof of concept study. (8th February 2021) - Perdreau, E; Jalal, Z; Walton, R; Sigler, M; Cochet, H; Naulin, J; Quesson, B; Bernus, O; Thambo, JB
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): National Research Agency (ANR) French Federation of Cardiology : "Aide à la recherche par équipe 2018, Cardiopathies de l'enfant" Introduction: After percutaneous implantation of an atrial septal defect (ASD) occluder device, a complex healing process leads to the device coverage within several months. However, an unexplained incomplete device coverage is at risk of complications such as thrombosis or infectious endocarditis. Purpose: The aim of the study was to assess the device coverage process of ASD occluder devices in a chronic sheep model using micro-CT technology. Methods: After percutaneous creation of an ASD by catheterization, 8 ewes (mean age 5.4 ± 0.7 yo and mean weight 55.6 ± 7.9 kg) were implanted with a 16-mm Nit-Occlud ASD-R occluder (PFM medical, Cologne, Germany) and were followed for 1 month (N = 3) and 3 months (N =5). After heart explantation, a iodine contrast agent was used to enhance the tissue signal. The device coverage was then assessed by micro-CT and the results were compared to histology, used as the gold standard for healing evaluation. The micro-CT image resolution was 41.7 µm. Reconstruction was performed in 2D and 3D with Amira® software, allowing to obtain images that were exploited by a code to measure the surface for each disk of the analyzed devices. Histological study was performed after resin embedding and Richardson blue staining was used.  The pathologist was blinded to the duration of animals' follow-up and micro-CT results. Results: ASD creation and device closure was successful in 100% animals without complications. Following heart explantation, macroscopic assessment of devices showed that the coverage was complete for the left-side disk regardless of the duration of the follow-up and variable for the right-side disk, depending of the protrusion of this disk. 2D and 3D micro-CT analysis allowed an accurate evaluation of device coverage of each disk and was overall well correlated to histology slices (cf Figure). Surface calculation from micro-CT images showed that the median surface of coverage was 93 ± 8% for the left-side disk and 55 ± 31% for the right-side disk. Conclusion: This preliminary study made the proof of concept that micro-CT is a reliable tool to assess the coverage of intra-cardiac occluders in vitro. The translation to clinical practice is challenging but would allow an individual follow-up, to avoid thrombotic or infective complications.